Identification of factors affecting quality of multimodal transportation for containerised export in Indian scenario. (2018) - Dua, Aman; Sinha, Deepankar
This work explores the perception of actors in multimodal transportation to arrive at the significant factors influencing the quality of multi-modal transportation for containers from the India. The existing literature focuses on a particular issue, or some issues, such as cost, time or infrastructure related to logistics or concerns of a firm in maintaining efficacy of logistics operations. In this research, an attempt has been made to compile and analyse the major relevant issues and challenges of the primary stakeholders associated with multimodal transportations. The responses of the stakeholders, represented by the managers of the firms, in the logistics chain have been obtained through semi-structured interviews. The responses have been analysed qualitatively, and the summary of the results have been vetted by the respondents. The customers' perspectives have been further obtained by analysing their comments on the social networking websites of logistics firms. These e-comments have been analysed using SentiStrength, data mining software. The results of the analyses reveal the factors affecting the perception of stakeholders about the quality of multimodal transportation.